تصنيع المعجم العربي الجاوي للمتحدثين الجاويين في تسهيل بحث معنى المفردات العربية - Nur Hasan (VICRATINA, 2020)
This research is a bi-lingual Arabic-Java dictionary and is considered a scientific study between Arabic and Javanese. The purpose of this study is to try to legalize and facilitate the translation of Arabic vocabulary into Java language and its use of explanatory captions, contribute to the dissemination of the Arabic language and Islamic culture in the Javanese-speaking community, and facilitate the acquisition of Arabic vocabulary and its improved use in its semantic and functional contexts. The researcher used the method of alphabetical order, where the entries of this dictionary arrange alphabetical order, taking into account the level of the avant-garde learners, in terms of ease of handling and quick access to the required vocabulary. The result of this research is that this lexicon will help to develop the curriculum of the Arabic language for the speakers of Java, and it is a qualitative addition to the teaching aids used and helps them to overcome the difficulties faced by Java-speaking Arabic language learners. Keywords : Bilingual dictionary, Arabic-javanese, facilitating learners,  arabic                          vocabulary.